Real wage cyclicality of job stayers, within-company job movers, and between-company job movers - Paul J. Devereux; Robert A. Hart (Institute for the Study of Labor (IZA), 2005)
Using the British New Earnings Survey Panel Data (NESPD) for the period 1975 to 2001 we estimate the wage cyclicality of job stayers (those remaining within single jobs in a given company), within company job movers, and between company job movers. We also examine how the proportion of internal and external job moves varies over the business cycle. We find that the wages of internal movers are slightly more procyclical and wages of external movers considerably more procyclical than those of stayers. Notwithstanding, a decomposition shows that in Britain, wage cyclicality arises almost entirely from the procyclicality of wages for job stayers, with across- and within-firm mobility playing a lesser role. Thus, there is little evidence for rigid wage models that imply that employers use changes in job titles as a means of adjusting wages to the business cycle. We also show that the distinctions between private and public sectors and between workers covered and uncovered by collective agreements have important impacts on the wage estimates of both stayers and movers.
Keywords: E32; J31; 330; wage cyclicality; job stayers; internal job movers; external job movers; Reallohn; Arbeitsmobilität; Interner Arbeitsmarkt; Großbritannien